2011
DOI: 10.1007/s11033-011-1075-9
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor gene -173G>C polymorphism and risk of bladder cancer in southeast China: a case–control analysis

Abstract: Inflammatory factors may promote carcinogenesis. Macrophage migration inhibitory factor (MIF), which is derived from T-cell, known as a member of the transforming growth factor-β (TGF-β) superfamily, plays an important role in the pro- and anti-inflammatory response to infection and in the etiology of bladder cancer. We hypothesized that MIF-173 locus polymorphism might contribute to genetic susceptibility to bladder cancer. In a hospital-based case-control study of 325 patients with bladder cancer and 345 can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Studies in patients from the Chinese mainland showed a RR of 5.85 for developing TCC after kidney transplantation when exposed to Chinese herbs. Furthermore, infection with high-risk HPV (especially HPV16; Li et al , 2011) and various gene polymorphisms (Yuan et al , 2012; Xie et al , 2013) have been postulated to have a role in bladder carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in patients from the Chinese mainland showed a RR of 5.85 for developing TCC after kidney transplantation when exposed to Chinese herbs. Furthermore, infection with high-risk HPV (especially HPV16; Li et al , 2011) and various gene polymorphisms (Yuan et al , 2012; Xie et al , 2013) have been postulated to have a role in bladder carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies assessed prostate cancer; 20 , 22 , 26 three studies assessed leukemia 17 , 19 , 25 and one each for gastric cancer, 24 cervical cancer, 18 colorectal cancer, 21 and bladder cancer. 23 The genotype distribution in one study deviated from HWE. 26 The main characteristics of all the included studies are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 94%
“…Only one study reported that MIF −173G/C polymorphism is associated with a decreased risk of cancer. 23 All the other studies reported the opposite conclusion. We also found a meta-analysis that investigated the association between the MIF −173G/C polymorphism and cancer risk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…MIF is a constitutively expressed protein produced in many cell types, including parenchymal and NPCs within the liver. MIF is associated with pathology of multiple liver diseases, including viral hepatitis, nonalcoholic and alcoholic liver disease, cirrhosis, and hepatocellular carcinoma [20][21][22][23][24]. To date, there has only been one study that examined the role of MIF in hepatic fibrosis.…”
Section: Introductionmentioning
confidence: 99%